LEVELS AND TYPES OF MANIFESTATIONS OF SOCIAL-POLITICAL “AGREEMENT-DISAGREEMENT” - S. I. Nekrasov; O. M. Khokhlowa (Научный вестник МГТУ ГА, 2016)
The article deals with the basic levels and types of manifestation of social and political agreement and disagreement. An original model of levels and types of dichotomy "agreement and disagreement" on the basis developed typology of political subjects. In the abovementioned dichotomy such typos of agreement and disagreement as “solidarity - egocentrism”, “consensus - protest”, “constructive active - destructive active” independently.